The Students’ Intrinsic Motivation for Learning Non-Financial Information Matters from Their Self-Identification as Global Citizens - Albuquerque, Fábio; Dias, Ana Isabel; Domingos, Alexandra (Sustainability, 2023)
Recent developments related to non-financial information (NFI) reporting encourage the adoption of a long-term vision approach to sustainable development, which is also behind the definition of global citizens. In turn, the self-determination theory (SDT) describes which elements explain the students’ motivation. Using NFI as the subject and the SDT as the theoretical framework, this paper aims to identify the elements that can explain accounting students’ intrinsic motivation to learn topics related to NFI. Those elements include the different aspects that integrate the concept of a global citizen as well as sociodemographic variables. Data were gathered from a questionnaire to accounting students in Portugal. Through factorial analysis and linear regression, the findings indicate that all the elements underlying the concept of a global citizen, except empathy, are relevant in explaining students’ intrinsic motivation. Conversely, sociodemographic variables were not relevant for this purpose, which may indicate a more integrated perspective of the learning usefulness of topics related to NFI by self-identified students as global citizens. This paper provides insights into how students of an accounting course are intrinsically motivated to acquire skills in NFI reporting, which is particularly relevant to higher education institutions (HEIs), professors, students, and organizations related to accountancy education.